Cover Image. (25th January 2018) - Unknown
Abstract : Cover Art: Adipose tissue-derived stromal cells (ASC) induce endothelial cells vessel-like network formation in three-dimensional microenvironments. ASC (CM-Dil-labeled, red) and HUVEC (PECAM-1, green) were embedded in Matrigel. Nuclei were stained with 4′, 6-diamidino-2-phenylindole (blue). Confocal microscopy with z -stack acquisition was used to reconstruct the image. See Terlizzi et al. beginning on page 240 .